2013
DOI: 10.11118/actaun201260060111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different extenders on ram sperm traits during storage

Abstract: The aim of the study was to test commercial extenders used for short-term and long-term sperm preservation. Semen was collected in the reproduction season, i.e. from June to December. The ejaculates were obtained from single services and the routine analysis of the semen was performed immediately after the collection. The examination included semen volume, colour and texture, sperm concentration and motility, ejaculate turbulence and percentage of sperm with abnormal morphology. The semen was diluted with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Sperm viability after storage at 4 o C varied with extender in ram (Rakha et al, 2013). Previous studies observed that Triladyl showed better sperm viability after 24 h (81.2%) of storage at 4 o C compared with semen stored in other extenders (78.6% for Andromed or 77.9% for Biladyl; Hegedűšova et al, 2012). In order to get a satisfactory conception rate, cold semen should have >70% viable spermatozoa in bovine (Nilani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm viability after storage at 4 o C varied with extender in ram (Rakha et al, 2013). Previous studies observed that Triladyl showed better sperm viability after 24 h (81.2%) of storage at 4 o C compared with semen stored in other extenders (78.6% for Andromed or 77.9% for Biladyl; Hegedűšova et al, 2012). In order to get a satisfactory conception rate, cold semen should have >70% viable spermatozoa in bovine (Nilani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The most common semen extenders for sheep are based on Tris and egg yolk. There were studies conducted to compare ram semen quality after chilling diluted with commercial extenders (Kasimanickam et al, 2011;Hegedűšova et al, 2012). However, there are no reports regarding chilled preservation of indigenous ram semen with commercial specially Triladyl and tris fructose egg yolk (TFE) extenders and their effects on PR in Indigenous ewes in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Many kind of extenders like TRIS-egg yolk, skim milk, sodium citrate-egg yolk, coconut milk etc. are used in addition to many other traditional extenders successfully in preserving ram semen (Hegedusova et al, 2012). El-Gaafary (1987) suggested that skim milk extender was found to be a good medium for preserving the fertilizing capacity of ram spermatozoa for three h at 5ºC during storage.…”
Section: Introductionmentioning
confidence: 99%